STRATEGY OF SMEs IN THE COVID-19 PANDEMIC PERIOD - Agustina Prativi Nugraheni; Octavia Lhaksmi Pramudyastuti; Suci Nasehati Sunaningsih (Sekolah Tinggi Ilmu Ekonomi Jayakarta, 2020)
The covid-19 pandemic that is happening right now has a global impact. In the field of economy, this pandemic cause consumer purchasing power has declined. The decline in consumer purchasing power can result in businesses experiencing a turn over and even closing down. Facing this covid-19 strategy is needed to be able to sustain the business. This study aims to analyze the strategies carried out by SMEs during the pancemic. This research is a qualitative research with a case study approach. The research data obtained through surveys and respondents in this study were 33 SMEs in the field of crafts in Solo. The results showed that SMEs had implemented a strategy that included improving product quality, improving service quality and utilizing technology